Check-list and conservation state of the mammals of National Park el Chico, Hidalgo, Mexico - Hernández-Flores, S.D.; Rojas-Martínez, A.E. (Instituto de Ecología, A.C., 2010)
We present a check-list of mammals of El Chico National Park based in field surveys realized between years 2004 to 2008. The mammals identificated were 30 species and 11 are recorded for the first time in the park: Glaucomys volans, Peromyscus melanotis, Reithrodontomys megalotis, R. sumichrasti, Spilogale gracilis, Cryptotis mexicana, Sorex saussurei, Dermanura azteca, Corynorhinus towsendii, Eptesicus fuscus, Lasiurus cinereus, Myotis californicus y M. velifer. The most abundant species belonged to Rodentia and Carnivora. Threatened species account for 16.67 % of the richness (C. mexicana, S. saussurei, Sciurus oculatus, G. volans y Corynorhinus mexicanus). Mammals in this park are threatened by human settlements and excessive tourism. El Chico National Park is important for conservation and management of mammals as 23.8% of the mammalian diversity of the State of Hidalgo.